Innovations in XML applications and metadata management advancing technologies - Ramalho, José Carlos; Simões, Alberto; Queirós, Ricardo 1975- (Premier reference source, 2013)
"This book addresses the functionality between XML and its related technologies toward application development based on previous concepts" - Provided by publisher